Local Cultures of Advice Tie Formation - Roth Philip; Scheidgen Katharina (Journal of Organizational Sociology)
Informal social networks and especially advice networks are a key subject of organizational sociological research. The formation of these networks has so far been explained on the basis of universal tie-formation mechanisms. However, recent conceptual contributions suggest that tie formation practices follow cultural rules that may vary across social contexts. In our paper, we substantiate this argument empirically. Based on rich qualitative data, we compare advice tie formation (a) between two entrepreneurial communities and (b) between three research and development departments of large enterprises. We show that both impact and configuration of tie formation mechanisms systematically differ between comparable contexts. Building on our findings, we finally formulate propositions describing which advice network structures can be expected in specific cultures.